Corrigendum: Diabetes Knowledge, Attitudes, and Practices in adults with type 2 diabetes at primary health care clinics in Kimberley South Africa - Moses Alenbalu; Chika K. Egenasi; Wilhelm J. Steinberg; Omololu Aluko (South African Family Practice)
No abstract available.